Experimental investigation on the lateral structural performance of a traditional Chinese pre-Ming dynasty timber structure based on half-scale pseudo-static tests. (15th July 2018) - Meng, Xianjie; Yang, Qingshan; Wei, Jianwei; Li, Tieying
Highlights: The timber structure displays excellent deformation recovery ability. Energy dissipation capacity and deformability are hardly affected by loading course. Lateral stiffness decreases with varying extents under various loading courses. A simplified bilinear elasto-plastic restoring force model is developed. Abstract: Existing ancient Chinese timber buildings are frequently subjected to seismic or strong wind loads throughout their lifetime, hence their lateral structural performance can undergo significant changes. It is essential to employ tests in the laboratory to study these variations to protect these existing timber buildings. In this paper, a single-layer model of a timber building with a geometrical ratio of 1:2 was fabricated according to the pre-Ming dynasty construction method. Six pseudo-static tests were conducted under three levels of vertical loads. The timber structure displayed visible rocking characteristics during the tests, and the column feet and mortise-tenon joints were the weak links in the structure. The features of hysteresis curves, envelope curves, strength reduction, energy dissipation, and lateral stiffness of the timber structure were obtained, and their variations associated with loading courses were discussed. Moreover, a simplified restoring force model was built for this type of timber structure.